Implementasi Media Pembelajaran Interaktif Berbasis Android pada Materi Bangun Ruang Siswa Kelas V SD - Sari, Arissona Dia Indah; Romadhon, Wahyu Agung Mustikaning; Fauziyah, Nur (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to improve the understanding of grade V students about the material of three-dimensional shape (cubes and rectangular prism) by using interactive learning media based on Android. This class action research was conducted in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The subjects of this research involved 23 students of class V UPT SDN 08 Gresik who were between 10 and 11 years old. Data was collected through tests, observation sheets, and questionnaires. The results showed there was a significant increase in students' understanding. The average score of cycle I was 66,6 and 76,6 in cycle II. The percentage of student learning completeness increased from 45,5% in cycle I, and 83,3% in cycle II. The use of Android based interactive learning media proved effective in improving students' understanding as well as their engagement in learning.